Assessing the compatibility of Ethiopia’s reservations and ‘interpretative declarations’ with the Maputo protocol’s object and purpose - Diallo, Papa Fara (University of Pretoria, 2023)
Dissertation (LLM ( (Human Rights and Democratisation in Africa))--University of Pretoria, 2022.